1992
DOI: 10.1152/ajpcell.1992.262.6.c1371
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocytes from magnesium-deficient hamsters display an enhanced susceptibility to oxidative stress

Abstract: Previous studies in our laboratory have indicated a role for free radical participation in magnesium deficiency cardiomyopathy. We have demonstrated the ability of various antioxidant drugs and nutrients to protect against magnesium deficiency-induced myocardial injury. In this study, we have examined erythrocytes from normal and magnesium-deficient animals and compared their susceptibility to an in vitro oxidative stress. Syrian male hamsters were placed on either magnesium-deficient or magnesium-supplemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
1
2

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 11 publications
3
49
1
2
Order By: Relevance
“…Magnesium also influences superoxide dismutase activity in retinal tissue [19]. Magnesium is required for glutathione biosynthesis and its depletion has been associated with decreased antioxidant properties [68,69]. Oxidative stress is involved in glaucoma pathogenesis [70].…”
Section: J Clin Exp Invest Wwwjceionlineorg Vol 4 No 2 June 2013mentioning
confidence: 99%
“…Magnesium also influences superoxide dismutase activity in retinal tissue [19]. Magnesium is required for glutathione biosynthesis and its depletion has been associated with decreased antioxidant properties [68,69]. Oxidative stress is involved in glaucoma pathogenesis [70].…”
Section: J Clin Exp Invest Wwwjceionlineorg Vol 4 No 2 June 2013mentioning
confidence: 99%
“…Increased oxygen free radical production, which may contribute to several human diseases, 31 is associated with both low plasma GSH/GSSG ratios 4 and with low intracellular magnesium concentrations, 16 and antioxidants drugs or nutrients such as ␣-tocopherol, 15,32,33 probucol, and captopril 33 have been demonstrated to protect against magnesium deficiency-associated cerebral vascular damage 32 and magnesium deficiency-induced myocardial injury. 15,17,33 Conversely, prior magnesium depletion renders cells more sensitive to oxidative damage. 15,17 Furthermore, magnesium may itself possess antioxidant properties, scavenging oxygen radicals, possibly by affecting the rate of spontaneous dismutation of the superoxide ion.…”
Section: Barbagallo Et Almentioning
confidence: 99%
“…15,17,33 Conversely, prior magnesium depletion renders cells more sensitive to oxidative damage. 15,17 Furthermore, magnesium may itself possess antioxidant properties, scavenging oxygen radicals, possibly by affecting the rate of spontaneous dismutation of the superoxide ion. 34 Chronic hypomagnesemia results in excessive production of oxygen-derived free radicals, 33 supporting a role for magnesium in altering the threshold antioxidant capacity.…”
Section: Barbagallo Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…1994). Babesia belong to the same phylum of protozoan parasites as Plasmodium and Mg deficiency is known to exert an increased oxidative stress on erythrocytes in hamsters (Mesocricetus auratus; Freedman et al 1992). In his pioneering studies, Godfrey (19576) showed that fish oil in a low-vitamin E diet protected against Babesia rodhaini in mice.…”
Section: Malariamentioning
confidence: 99%